Предмет: Алгебра,
автор: Margorito2911
Решите уравнение (3х-5:2)- (2х-3:3)=4-х В скобках дробь
Ответы
Автор ответа:
0
Умножаем правую и левую часть на 6, получаем:
((3x-5)*6)/2-((2x-3)*6)/3=4x*6
9x-15-4x+6=24x
9x-4x-24x=15-6
-19x=9
x=9/(-19)
((3x-5)*6)/2-((2x-3)*6)/3=4x*6
9x-15-4x+6=24x
9x-4x-24x=15-6
-19x=9
x=9/(-19)
Похожие вопросы
Предмет: Литература,
автор: zxckoil
Предмет: Английский язык,
автор: arinasandybina12
Предмет: Литература,
автор: Аноним
Предмет: Математика,
автор: маря72
Предмет: Математика,
автор: камиль15ска